THE CONCEPT OF BEHAVIOR OF PRODUCERS PERSPECTIVE YUSUF QARDHAWI: STUDY ON THE FIVE FEET VENDORS AT TANJUNG JAYA MARKET, CENTRAL LAMPUNG - Lisda Aisyah; Haris Faulidi Asnawi; Galih Aisya (Journal of Management and Islamic Finance, 2021)
The efforts of producers to obtain maximum benefits can be realized if producers apply Islamic values. The benefits and blessings obtained by the producers are one thing that will contribute to the achievement of falah. Yusuf Qhardhawi has stated that there are 4 pillars that must be carried out by a Muslim producer. In this way, the producer will obtain essential happiness, namely glory not only in the world but also in the end. The purpose of this study is to analyze how the behavior of Muslim producers among street vendors in Yusuf Qhardhawi's perspective (Study on street vendors in Tanjung Jaya Market, Lampung Tengah. The research method used is qualitative descriptive method. From the results of this study, it can be seen that the four main pillars for behaving according to the behavior of Muslim producers are stated by Yusuf Qardhawi, namely: Godhead (Robbaniyyah), Ethics (Akhlaqiyyah), Human resources (Insaniyyah) and balance (Washaty), only 2 pillars practiced namely the pillar of human resources and balance, while the pillars of divinity and ethics are not all street vendors apply these pillars in practice. This is the proof that street vendors in the Tanjung Jaya market, Lampung Tengah, have not been in accordance with the behavior of Muslim producers according to Yusuf Qardhawi.Â